Prinsip-prinsip Etika Kristen untuk Menghadapi Moralitas dalam Keluarga dan Komunitas - Befirman Jaya Laia; Gugun Gugun; Anggi Laurenchia; Sandra Rosiana Tapilaha (Pusat Riset dan Inovasi Nasional, 2025)
Christian education, which is based on the teachings of the Christian religion, has an important role in forming individual character and morals. This education system aims to instill Christian moral and ethical values in students as a guide throughout their lives. However, in the modern era which is full of dynamics and change, Christian education faces big challenges in overcoming moral decline in society. Technological developments, cultural changes, and greater access to information create an increasingly complex moral landscape. Thus, Christian education has a key role in shaping individual character and morals and providing a solid ethical foundation, although there are a series of challenges that hinder its effectiveness. This research explores how Christian ethical principles guide interactions within families and communities, as well as their role in facing moral challenges in the modern era. The family is the main center in the formation of individuals and society, where values and ethics are practiced and passed from one generation to the next. This study emphasizes the importance of respecting parents as a spiritual basis that shapes the character and morality of Christian families. Generations, born in the digital era, are faced with various moral and ethical challenges. Christian education in the family environment can provide a strong moral foundation to face the pressures and temptations around them. Character is not a fixed trait, but rather the result of various influences in a person's life. Christian education provides a deep spiritual dimension, teaching ethical values, compassion, and commitment.